Gender inequality, land rights and socio-economic transformation: historical studies and theoretical analysis of women’s right to land under the law of thesawalamai. - Purathani, M.; Swaminathan, J.M. (The Sri Lanka Journal of South Asian Studies, 2017)
Land is considered as a means not only to generate an income, but also to empower women and minimize their dependency. However, there is a disparity in owenrship of property due to the pluralistic nature of a legal system that prioritizes discriminatory customary and religious laws. In this context, this paper focuses on the Thesawalamai law, one of the customary laws of Sri Lanka that deprives and discriminates the married women of their right to land. The disinclination to repeal the discriminatory provisions was sustained on the ground that the repeal or revision of such provisions would be very sensitive as they were derived from the inherent customary practice of the Tamils in North and are constitutionally guaranteed. Based on a mixed method analysis, this paper revisits the history and claim that the marital power of husbands which is being instrumental in discriminating the married women, was not an inherent customary practice of the early settlers, rather brought by the subsequent patriarchal peasants and legitimized by colonial legislations and judicial pronouncements. It further analyses the impact of the discriminatory provisions on the transformation of women’s roles, particularly in the post-armed conflict context through a survey, before suggesting the possible means to engendering the Thesawalamai.
Keywords: Gender inequality; Right to land; Thesawalamai; Socio-economic transformation; Post-armed conflict